Noninvasive measures of brain edema predict outcome in pediatric cerebral malaria - Kampondeni, Samuel; Birbeck, Gretchen; Seydel, Karl; Beare, Nicholas; Glover, Simon; Hammond, Colleen; Chilingulo, Cowles; Taylor, Terrie; Potchen, Michael (Surgical neurology international, 2018)
Background: Increased brain volume (BV) and subsequent herniation are strongly associated with death in pediatric cerebral malaria (PCM), a leading killer of children in developing countries. Accurate noninvasive measures of BV are needed for optimal clinical trial design. Our objectives were to examine the performance of six different magnetic resonance imaging (MRI) BV quantification measures for predicting mortality in PCM and to review the advantages and disadvantages of each method. Methods: Receiver operator characteristics were generated from BV measures of MRIs of children admitted to an ongoing research project with PCM between 2009 and 2014. Fatal cases were matched to the next available survivor. A total of 78 MRIs of children aged 5 months to 13 years (mean 4.0 years), of which 45% were males, were included. Results: Areas under the curve (AUC) with 95% confidence interval on measures from the initial MRIs were: Radiologist-derived score = 0.69 (0.58-0.79; P = 0.0037); prepontine cistern anteroposterior (AP) dimension = 0.70 (0.56-0.78; P = 0.0133); SamKam ratio [Rt. parietal lobe height/(prepontine AP dimension + fourth ventricle AP dimension)] = 0.74 (0.63-0.83; P = 0.0002); and global cerebrospinal fluid (CSF) space ascertained by ClearCanvas = 0.67 (0.55-0.77; P = 0.0137). For patients with serial MRIs (n = 37), the day 2 global CSF space AUC was 0.87 (0.71-0.96; P < 0.001) and the recovery factor (CSF volume day 2/CSF volume day 1) was 0.91 (0.76-0.98; P < 0.0001). Poor prognosis is associated with radiologist score of ≥7; prepontine cistern dimension ≤3 mm; cisternal CSF volume ≤7.5 ml; SamKam ratio ≥6.5; and recovery factor ≤0.75. Conclusion: All noninvasive measures of BV performed well in predicting death and providing a proxy measure for brain volume. Initial MRI assessment may inform future clinical trials for subject selection, risk adjustment, or stratification. Measures of temporal change may be used to stage PCM.